Analisis asosiasi merek terhadap respon konsumen pada merek Hedonik dan merek Utilitarian - Henryanto, ABAHARIS ([Yogyakarta] : Universitas Gadjah Mada, 2006)
This study was intended to test the brand association to consumer response at hedonic brand and utilitarian brand. Especially on the effect of dimensions brand function (guarantee function, personal identification function, social identification function, and status function) to consumer response (brand extension, recommendation and consumer willingness to pay at price premium). The model of this research is firstly advanced by Bele’n del Rio et al., (2001) in his article entitled “The effects of brand functions on consumer response.” The subjects of this study were193 students to hedonic brand and 197 students to utilitarian brand who lived in Daerah Istimewa Yogyakarta (DIY). By using analysis instrument of Structural Equation Modeling in AMOS 4.01 program. The results of the analysis suggested on the hedonic brand had effects of dimensions brand function to consumer response, especially on personal identification and social identification. But on the utilitarian brand, from twelve hypotheses proposed were unsupported in this study.